Metabolic response of the sea cucumber Apostichopus japonicus during the estivation-arousal cycles - Zhao, Ye; Wang, Haona; Wang, Han; Pi, Yongrui; Chen, Muyan (Frontiers in Marine Science, 2022)
Estivation is a widespread survival strategy for dealing with adverse environmental conditions such as high temperature, low oxygen and lack of water or food, which has been reported across multiple vertebrate and invertebrate species. The sea cucumber Apostichopus japonicus is an excellent model organism to investigate the adaptive mechanism of estivation in marine invertebrates. In this study, a metabolomics approach based on ultraperformance liquid chromatography coupled with electrospray ionization time-of-flight mass spectrometry (UPLC-ESI-Q-TOF/MS) was performed to reveal the metabolic response of intestines from adult A. japonicus over the annual estivation-arousal cycle: nonestivation (NA), deep-estivation (DA) and arousal from estivation (AA). A total of 424 metabolites were identified, and among them, 243, 238 and 37 significant differentially metabolites (DMs) were further screened in the comparisons of DA vs. NA, AA vs. DA, and AA vs. NA. Specifically, the levels of metabolites involved in glycolysis and the tricarboxylic acid cycle were significantly decreased, while higher amounts of long-chain fatty acids, phospholipids and free amino acids were found in A. japonicus during estivation, implying that sea cucumbers might reorganize metabolic priorities for ATP production by depressing carbohydrate metabolism and promoting lipid and amino acid catabolism. Interestingly, elevated relative carbon flow entry into the pentose phosphate pathway and accumulation of various nonenzymatic antioxidant molecules (e.g., tocotrienols, folic acid, catechin, genistein and resveratrol) were observed in estivating sea cucumbers, which suggested that enhancement of the reactive oxygen species defense system might promote long-term viability in the hypometabolic state in an energy-efficient manner. Thus, this research provides new insights into the adaptation mechanisms of marine invertebrates to estivation at the metabolic level.